Traumatic Brain Injury in Adolescence and the Family Resilience Process: A Case Study - Jérôme Gauvin-Lepage RN, PhD (SAGE Publishing, 2019)
Introduction The aim of this study was to better understand the family resilience process following a severe traumatic brain injury during adolescence. Case Presentation Inspired by the humanistic model of nursing care as a disciplinary perspective, this study used a qualitative and inductive case study design. Management and Outcome The data analysis yielded six themes as well as four subthemes that illustrate this family's resilience process. The most important factors that emerged are (a) family characteristics (i.e., a fighter personality , cultural and spiritual beliefs, presence of hope, keeping a sense of humor), (b) support of family members, (c) support of friends, (d) practicing sports and leisure activities, (e) back-to-school support, and (f) feeling helpful to the adolescent. Discussion This study provides interesting avenues with regard to the implementation of strategies to foster the resilience process in families during particularly difficult situations in their lives, such as a traumatic brain injury during adolescence.